Figures of substitution used in the language of advertising in some Vietnamese and English advertisements - Phùng, Thanh hà (College of Foreign Languages, 2017)
In particular, I will focus on how this comic influences the usage of vocabulary as well as how their interaction is enabled. Also, the study will test the usefulness of using picture-based text in teaching English of all levels. Through the attraction and varieties of the comic, I hoped to tap the enthusiasm of my students towards learning English and make them active participants in their own instruction.